2013
DOI: 10.1108/msq-03-2013-0037
|View full text |Cite
|
Sign up to set email alerts
|

Service recovery's impact on customers next-in-line

Abstract: Purpose -Previous research considers service recovery as a one-on-one interaction between a service provider and a complaining customer. However, customers frequently complain at the place where they receive the service, making an investigation of the impact of a service recovery on observing customers necessary. Using observational learning theory and attribution theory as theoretical anchors, this paper examines whether observing a service recovery influences the observing customers' satisfaction and repurch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 51 publications
4
64
0
2
Order By: Relevance
“…This concurs with the offline observations of Van Vaerenbergh et al (2013). Although we do not know how the stories of service incidents posted online might affect those silent online viewers, we have observed that online participants in the C2C forum do re-shape their perceptions and expectations about a service and a company.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This concurs with the offline observations of Van Vaerenbergh et al (2013). Although we do not know how the stories of service incidents posted online might affect those silent online viewers, we have observed that online participants in the C2C forum do re-shape their perceptions and expectations about a service and a company.…”
Section: Discussionsupporting
confidence: 86%
“…However, research is beginning to examine the impact of one customer's experiences of service recovery on the attitudes and behaviours of other customers (Van Vaerenbergh et al, 2013). Online channels, such as customer complaint forums, provide service customers with the opportunity to interact with one another, learn from other customers' complaints, and participate in the service recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have examined reactions to overheard service failures and failed recoveries involving interactions between either adjacent customers/frontline employees (path e) or adjacent customers/managers (path g). For example, across two studies, Van Vaerenbergh et al (2013) find that customers who observe frontline employees treat a complaining customer in an uncivil manner report lower satisfaction, perceived service quality, and return intentions, with stronger effects when the customer is not to blame for the failure. More recently, Mattila et al (2014) show that observers who witness a manager respond in an uncivil manner to a complaining customer report greater anger and negative word of mouth, and lower perceived justice, return intentions, and positive word of mouth, effects which were stronger when observers adopted an experiential (vs. rational) processing frame.…”
Section: Observed Service Failures Failed Recoveries and Incivilitiesmentioning
confidence: 99%
“…Given their ubiquity, an important question for hospitality managers and researchers is how, why, and when observing uncivil behaviors influences customers. Notably, a growing number of studies reveal that observed incivilities lead to anger, reduced satisfaction, reluctance to return to and recommend a service provider, and a desire to "get even" with the offending party (e.g., Casidy and Shin 2015;Mattila, Hanks, and Wang 2014;Melián-González and Bulchand-Gidumal 2017;Porath et al 2010Porath et al , 2011Van Vaerenbergh, Vermeir, and Larivière 2013;Wan, Chan, and Su 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Service recovery management plays an important role in determining whether or not the customer is satisfied with his or her retail service experience. Successful complaint management is likely to lead to positive evaluations of the retailer and an increase in satisfaction (Hsin-Hui, Yi-Shun, and Li-Kuan, 2011; Levesque and McDougall, 1996;Nyer, 2000) and thus repurchasing likelihood (Fornell and Wernerfelt, 1987;Vaerenbergh, Vermeir, and Lariviere, 2013) since it gives complaining customers the opportunity to let loose their anger and to redress failed shopping experiences. Noticeably, in an attempt to measure customer responses to service failure and post-recovery satisfaction, Goodwin and Ross (1992), in an experiment, manipulate levels of complaint outcome, apology and voice regarding service in dentistry, airlines, auto repairs and restaurants.…”
Section: Retail Service Quality Antecedentsmentioning
confidence: 99%